SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL TIGA LAPIS DARI KULIT BUAH DURIAN BERDASARKAN KONSENTRASI PEREKAT - Siallagan, Tamauli; Oramahi, H A; Nurhaida, . (JURNAL HUTAN LESTARI, 2016)
Durian skin is made into particles as a material for furniture. Durian skin made into coarse particles with a size of passing through an 8 mesh, retained on a 20 mesh and fine particles passes through a 4 mesh, restrained on 6 mesh. The bonding material used is formaldehyde urea concentration of 12%, 14% and 16%  with other additives such as catalysts, paraffin and liquid smoke. The particle board is made with a size 30cm x 30cm x 1cm, the desired density is 0.6 g/cm3. The making of particle board used compression heat at 1400C with a specific pressure of 25 kg / cm2 for ± 10 minutes. The testing of the physical properties of particle board (desity, moisture content and thickness swelling) and mechanical properties of particle board (modulus of elasticity, modulus of  rupture, internal bording and screw holding strength) were conducted in accordance with the standard JIS A5908-2003. The results showed that the physical properties that meet the standard JIS A5908-2003 were the density and  moisture content, and for mechanical properties that meet the standard JIS A 5908-2003 were the bonding strength and screw holding strength. The best bonding concentration for physical and mechanical properties of particle board from durian skin is at a bording concentration of 16%. Keywords : Durian skin, particle board, physical